Innovations in education: The development of a new pedagogical technology of a combinational type, focused on the development of personality of students - Vera Zhurakovskaya; Aleksandr Sichinava; Tatyana Simakova; Olga Olicheva; Sergey Rykov; Julya Valeeva; Anastasia Kulachinskaya; Svetlana Ilyashenko (Journal of Open Innovation: Technology, Market, and Complexity, 2020)
The paper considers the problem of adolescent and young students' personalities' development in the conditions of face-to-face and distance school learning. The scientific novelty of the study is the proposed classification of pedagogical technologies according to the degree of their novelty: modernized technology, combinational technology, progressive technology, pedagogical technology of the combinational type, the essence of which is shown in its title. A specific model of pedagogical technology of the combinational type "Teaching in cooperation, in a team using flipped classroom" was developed. The developed technology was implemented during the classes of the humanities and natural-mathematical cycles. Nine hundred and eight adolescent and young students (divided into experimental and control groups) and 32 teachers participated in the experimental work. To analyze the differences between the experimental and control groups in terms of the student's personality manifestation, several criteria and indicators were considered. For mathematical and statistical processing of the obtained results, the multifunctional statistical Fisher's F-test was used. Analysis of the implementation of the developed technology in the conditions of face-to-face and distance learning showed a positive dynamics of experience formation of the student's personality manifestation. This allowed the authors to consider the developed pedagogical means effective.
Keywords: 650; blended learning; combinational technology; distance learning; e-learning; flipped classroom; student personality